An evaluation of the accuracy of DEM-derived altitude and slope values - Byne, S.; Bell, William C.; Leclerc, Gregoire (International Center for Tropical Agriculture, 1995)
This project was set up to investigate the level of accuracy which can be expected for slope and altitude values derived from low-cost Digital Elevation Models (DEMs). Eight gridded DEMs were generated from digitized contour maps at a range of scales:1:10,000 1:25,000 1:100,000 1:200,000 - and using a range of contour intervals 25m, 50m and 100m. A Control DEM was then produced using large scale aerial photographs (1:28,000) which were registered for auto-extraction of z-values using Helava software and accuracy tested using 91 differentially measured GPS ground control points. The DEM showed an vertical RMSE of 4.26m which is well within the accuracy standards for a `level one` DEM as stipulated by the USGS. The altitude and slope readings derived from each of the eight test models were then compared to the values derived from the Control to assess the relationship between the cost of production of a DEM and the accuracy of the results. The relationship between cellsize and slope correlation was also examined Several recommendations have been made regarding optimal production methods for a DEM based on application needs.